Survival of the fittest: an examination of the High Park fire news meme lifecycle on news organizations' Facebook and web pages - Shugarts, Angela, author; Switzer, Jamie, advisor; Seel, Pete, committee member; Hoffman, Chad, committee member (Colorado State University. Libraries, 2013)
This study employs a mixed methods content analysis of 14 news organization's Facebook and website posts of the High Park fire news meme to identify the reasons behind how and why news memes propagate within social media and news website environments. This study gauges the feasibility of forecasting the spread of online news content based on specific features including photos, videos, article length, and span of time. News memes are defined as cultural units of information presented as written text, images, or videos whose existence is determined by the frequent behaviors of imitation and transmission, produced by media personnel from news organizations. The field of memetics, social media, and normative theories of the media serve as foundational areas for this study which extends the knowledge of the emerging domain of web memetics, which seeks to identify and track the evolution, spread, and implications of news memes by media personnel. Results show that specific characteristics (i.e. text, links, and photos) contributed to news meme propagation via reader comment contributions and likes. Additionally, results indicate that website environments are more frequent platforms for news memes to exist and thus perhaps more nurturing environments for High Park fire news memes to propagate within.
Keywords: social media; High Park fire; news memes; longevity; fecundity; fidelity